Thermopressure response type pressure-bearing acid-soluble plugging material and application thereof
Patent Information
- Application Number
- CN202211647420.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-21
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2042-12-21
AI Technical Summary
[0008]为解决储层段堵漏中桥堵材料封堵层承压不稳定易复漏的技术问题,本发明的目的在于提供一种一种温压响应型可酸溶承压堵漏材料及其应用,以满足不同温度、不同裂缝宽度、不同钻井液类型等条件下储层井漏承压堵漏需求
[0052]本发明的温压响应型可酸溶承压堵漏材料在地面配制和井下泵送过程中均保持惰性,进入漏层后在挤压和高温作用下,树脂发生熔融和固结,堵漏材料与漏层岩石壁面粘连,形成可酸溶的高强度致密封堵层,起到正反向承压堵漏效果。
Smart Images

Figure CN118222251B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of oil drilling technology, specifically to a temperature and pressure responsive acid-soluble pressure-bearing plugging material and its application. Background Technology
[0002] Well leakage problems severely impact exploration and development progress and efficiency improvement. Leakage occurs throughout the entire drilling and completion process, prolonging the drilling cycle, wasting significant amounts of drilling fluid and plugging materials, damaging the reservoir, and causing complex accidents such as stuck pipe, overflows, and even blowouts, resulting in substantial economic losses. Reservoir plugging materials are a hot research topic in solving well leakage problems, generally consisting of acid-soluble or oil-soluble particles and resin components.
[0003] CN202111047611.8 discloses an oil-soluble temperature-sensitive plugging agent for reservoir protection, comprising oil-soluble resin, modified asphalt, softening point regulator, crosslinking agent, and other components. It can melt and adhere within different temperature ranges, effectively sealing fractures. However, this oil-soluble temperature-sensitive plugging agent has a pressure-bearing capacity of less than 10 MPa, making it unsuitable for plugging leaks in oil-based drilling fluids and for pressure-bearing plugging operations in deep reservoirs.
[0004] CN201510276520.X discloses a bridging and plugging agent for fractured reservoirs, mainly composed of bridging materials, calcium carbonate particles, bitumen powder and acid-soluble fibers. It can seal fractures 1-5 mm wide, with a pressure bearing capacity of over 15 MPa and an acid solubility of over 70%. However, the plugging layer of this agent has insufficient resistance to shear failure and is prone to backflow under pressure fluctuations, leading to re-leakage.
[0005] CN103087687 A discloses an anti-backflow plugging agent, which is composed of the following components in parts by weight: 20-30 parts modified self-emulsifying epoxy resin-coated sand; 10-20 parts ultrafine calcium carbonate; 15-25 parts fibrous magnesia; and non-permeable agent NPL-2. However, this anti-backflow plugging agent is not applicable to a wide range of temperatures, its ability to improve the reverse bearing capacity of the bridging formulation in fractured formations is less than 5 MPa, and it cannot be acid-soluble.
[0006] CN201710385903.X discloses a low-density acid-soluble curing plugging agent, which includes components such as limestone powder, sepiolite fiber, and expanded resin. It has the characteristics of rapid strength development and no pollution to the reservoir. However, inorganic curing materials have long construction time, poor resistance to drilling fluid pollution, and construction risks under high temperature conditions.
[0007] Overall, bridging and sealing materials and curing materials (cement, downhole crosslinking, resin, etc.) are commonly used for sealing lost circulation in fractured formations. Bridging materials have poor adaptability to fractures, but under pressure fluctuations, the sealing layer is easily damaged and backflow occurs, leading to re-leakage. Cement, resin, and other curing materials have good adaptability to fractures and high compressive strength of the sealing layer, but they have disadvantages such as high construction risk, poor resistance to drilling fluid contamination, and poor acid solubility. Summary of the Invention
[0008] To address the technical problem of unstable pressure bearing and easy re-leakage in the sealing layer of bridging and plugging materials during reservoir well leakage plugging, the present invention aims to provide a temperature-pressure responsive acid-soluble pressure-bearing plugging material and its application to meet the pressure-bearing plugging requirements of reservoir well leakage under different conditions such as temperature, fracture width, and drilling fluid type.
[0009] To achieve the above objectives, the present invention provides a temperature and pressure responsive acid-soluble pressure-bearing sealing material, which includes resin-coated particles and pure resin particles.
[0010] The resin-coated particles comprise an internal phase and an external phase. By mass, the raw material of the internal phase comprises 60-90 parts of inert material, and the raw material of the external phase comprises 10-20 parts of modified resin, 1-20 parts of curing agent, and 1-5 parts of lubricant. The modified resin is a modified solid epoxy resin with triazine groups.
[0011] The pure resin particles are thermoplastic solid resin particles.
[0012] On the one hand, the temperature-pressure responsive acid-soluble pressure-bearing plugging material of the present invention remains inert during surface preparation and downhole pumping. After the plugging particles enter the leaking formation, they accumulate to form a sealing layer. Under the high temperature of the formation, the resin coating on the particle surface melts and solidifies, adhering to the rock wall of the leaking formation, thus achieving a positive and negative pressure-bearing plugging effect. On the other hand, the resin coating layer of the temperature-pressure responsive acid-soluble pressure-bearing plugging material of the present invention can dissolve under acidic conditions, and the inert particles it coats dissolve in acid, thereby protecting the reservoir.
[0013] Preferably, the modified solid epoxy resin with triazine groups has a softening point of 70-160℃ and is degradable under acidic conditions in the above-mentioned temperature-pressure responsive acid-soluble pressure-bearing sealing material.
[0014] Preferably, the preparation method of the above-mentioned temperature and pressure responsive acid-soluble pressure-bearing sealing material includes the following steps:
[0015] (1) Under nitrogen protection, hexahydrotrimethyl-S-triazine was reacted with epichlorohydrin for the first reaction at 100-120℃ for 2 h to obtain an intermediate. Then, unreacted epichlorohydrin was removed by vacuum distillation.
[0016] (2) The solid epoxy resin, bisphenol A and the intermediate are mixed and dissolved in a solvent, a catalyst is added, and a second reaction is carried out to obtain the modified solid epoxy resin with triazine group.
[0017] In the above-mentioned temperature and pressure responsive acid-soluble pressure-bearing sealing material, preferably, in the preparation method of the modified solid epoxy resin with triazine group, the first reaction condition is: reacting at 100-120℃ for 2 hours;
[0018] In the above-mentioned temperature and pressure responsive acid-soluble pressure-bearing sealing material, preferably, in the preparation method of the modified solid epoxy resin with triazine group, the molar ratio of hexahydrotrimethyl-S-triazine to epichlorohydrin is 1:5-1:8.
[0019] In the above-mentioned temperature and pressure responsive acid-soluble pressure-bearing sealing material, preferably, in the preparation method of the modified solid epoxy resin with triazine group, the second reaction condition is: reacting at 110-130℃ for 4-6 hours.
[0020] In the above-mentioned temperature and pressure responsive acid-soluble pressure-bearing and leak-sealing material, preferably, in the preparation method of the modified solid epoxy resin with triazine group, the mass ratio of solid epoxy resin: bisphenol A: intermediate in step (2) is 1:0.3-0.5:0.7-1.
[0021] In the above-mentioned temperature and pressure responsive acid-soluble pressure-bearing sealing material, preferably, in the preparation method of the modified solid epoxy resin with triazine group, the solid epoxy resin is a high softening point solid epoxy resin, and the solid epoxy resin is selected from solid epoxy resin E12, solid epoxy resin E06 or solid epoxy resin E03.
[0022] In the above-mentioned temperature and pressure responsive acid-soluble pressure-bearing sealing material, preferably, in the preparation method of the modified solid epoxy resin with triazine group, the amount of catalyst added is 0.05-0.1 wt% of the reactants, and the catalyst includes one or more of triphenylphosphine, triethanolamine, and trimethylbutylamine.
[0023] In the above-mentioned temperature and pressure responsive acid-soluble pressure-bearing sealing material, preferably, in the preparation method of the modified solid epoxy resin with triazine group, the solvent is toluene and / or xylene.
[0024] Preferably, the preparation method of the above-mentioned temperature and pressure responsive acid-soluble pressure-bearing sealing material includes the following steps:
[0025] (1) Under nitrogen protection, hexahydrotrimethyl-S-triazine was reacted with excess epichlorohydrin at 100-120℃ for 2 hours, and then unreacted epichlorohydrin was removed by vacuum distillation to obtain the intermediate.
[0026] (2) Mix the high softening point solid epoxy resin with bisphenol A and the intermediate obtained in step 1 in a reaction solvent, add a catalyst, and react at 110-130℃ for 4-6 hours.
[0027] (3) After cooling the reactants from step (2) to room temperature, remove the unreacted solvent by vacuum distillation, wash with water 3-5 times to remove the catalyst, and finally obtain the modified solid epoxy resin with triazine group.
[0028] Preferably, the inert material of the above-mentioned temperature and pressure responsive acid-soluble pressure-bearing sealing material includes one or more of the following: lightweight ceramsite, calcite, seashells, calcium carbonate, micro-manganese powder, and expanded graphite.
[0029] Preferably, in the above-mentioned temperature and pressure responsive acid-soluble pressure-bearing sealing material, the particle size of the inert material is 0.01mm-8mm.
[0030] Preferably, the curing agent of the above-mentioned temperature and pressure responsive acid-soluble pressure-bearing sealing material includes one or more of the following: dicyandiamide, m-phenylenediamine, diaminodiphenylmethane, diaminodiphenyl sulfone, phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, and pyromellitic anhydride.
[0031] Preferably, the lubricant in the above-mentioned temperature and pressure responsive acid-soluble pressure-bearing sealing material includes one or a combination of calcium stearate, zinc stearate, solid polyvinyl alcohol, and talc.
[0032] Preferably, the raw material of the external phase of the above-mentioned temperature and pressure responsive acid-soluble pressure-bearing sealing material further includes 0-5 parts of a curing accelerator, wherein the curing accelerator includes one or more of the following: triethylamine hydrochloride, benzyltriethylammonium chloride, 2-ethyl-4-methylimidazolium, imidazolium salt complex, and acetylhydrazine.
[0033] The above-mentioned temperature and pressure responsive acid-soluble pressure-bearing sealing material, preferably, is prepared by the following steps: heating the modified resin to melt, mixing the molten modified resin with an inert material to coat the surface of the inert material with the modified resin; cooling to the softening point of the modified resin, adding a curing agent and preferably a curing accelerator and mixing thoroughly; cooling again, adding a lubricant and mixing; cooling the mixture and then pulverizing it to obtain the resin-coated particles.
[0034] In the above-mentioned temperature and pressure responsive acid-soluble pressure-bearing sealing material, preferably, in the preparation method of the resin-coated particles, the heating temperature for melting the modified resin is 10-20°C above the softening point; the stirring time after adding the curing agent is 3-10 min; and the stirring time after adding the lubricant is 1-3 min.
[0035] Preferably, the preparation method of the above-mentioned temperature and pressure responsive acid-soluble pressure-bearing sealing material includes the following steps:
[0036] (1) Wash and dry the inert material;
[0037] (2) Heat the resin to 10-20°C above the resin softening point and stir the molten resin with the inert material for 5-10 minutes to ensure that the resin fully coats the surface of the inert material.
[0038] (3) Reduce the heating temperature to the resin lubrication point temperature, add the potential curing agent and curing regulator, and continue stirring for 3-10 minutes until the potential curing agent, curing regulator and resin coating are fully mixed;
[0039] (4) Add lubricant to the system obtained in step (3), cool down and continue stirring for 1-3 minutes;
[0040] (5) After cooling the product obtained in step (4), crush it to obtain resin-coated particles of different sizes.
[0041] Preferably, the aforementioned temperature- and pressure-responsive acid-soluble pressure-bearing sealing material comprises graded resin-coated particles and at least one type of pure resin particles, wherein the total weight ratio of the resin-coated particles to the total weight of the pure resin particles is 8-9:1-2. The particle size distribution of the temperature- and pressure-responsive acid-soluble pressure-bearing sealing material needs to be optimized for different crack widths.
[0042] Preferably, in the above-mentioned temperature and pressure responsive acid-soluble pressure-bearing sealing material, the raw material of the pure resin particles is a thermoplastic solid resin, and the softening point of the thermoplastic solid resin is 80-150℃.
[0043] Preferably, the thermoplastic solid resin of the above-mentioned temperature and pressure responsive acid-soluble pressure-bearing sealing material includes one or more of the following: modified solid epoxy resin with triazine group, linear phenolic resin, polyurethane, polyamide resin, and acrylic resin.
[0044] Preferably, in the above-mentioned temperature and pressure responsive acid-soluble pressure-bearing sealing material, the particle size distribution range of the graded resin-coated particles is 0.01-3mm.
[0045] Preferably, in the above-mentioned temperature and pressure responsive acid-soluble pressure-bearing sealing material, the particle size of the pure resin particles is 0.01-3mm.
[0046] The present invention also provides an application of the above-mentioned temperature and pressure responsive acid-soluble pressure-bearing plugging material in pressure-bearing plugging of reservoir sections.
[0047] In the above applications, preferably, the application temperature is 80-150℃.
[0048] In the above applications, preferably, the acid solubility of the temperature-pressure responsive acid-soluble pressure-bearing sealing material after solidification is >80%.
[0049] In the above applications, preferably, the temperature-pressure responsive acid-soluble pressure-bearing plugging material is added to the drilling fluid, which is a water-based or oil-based drilling fluid; based on the total volume of the drilling fluid, the total mass of the temperature-pressure responsive acid-soluble pressure-bearing plugging material is 25-40 (w / v)%.
[0050] In the above applications, preferably, the drilling fluid with added temperature- and pressure-responsive acid-soluble pressure-bearing plugging material has a 1-8 mm crack width and a positive or negative pressure of ≥15 MPa.
[0051] The technical solution provided by this invention has the following beneficial effects:
[0052] The temperature-pressure responsive acid-soluble pressure-bearing plugging material of the present invention remains inert during surface preparation and downhole pumping. After entering the leaking layer, the resin melts and solidifies under the action of extrusion and high temperature. The plugging material adheres to the rock wall of the leaking layer, forming an acid-soluble, high-strength, sealing plugging layer, which achieves positive and negative pressure-bearing plugging effect. Attached Figure Description
[0053] Figure 1 The image shows the solidified body formed by the temperature-pressure responsive acid-soluble pressure-bearing sealing material of Example 1 after being extruded at 10MPa for 20 minutes and heated at 80°C for 5 hours.
[0054] Figure 2A Scanning electron microscope images of the surface of 1-2 mm shell particles (×300x magnification);
[0055] Figure 2B The image shows a scanning electron microscope (SEM) image of the 1-2 mm resin-coated seashell particles in Example 2 (×300x magnification). The surface of the seashell particles becomes dense and smooth after being coated with resin.
[0056] Figure 3 The pressure test curves of the sealing materials in Example 4, Comparative Examples 4 and 5 are shown.
[0057] Figure 4A The photo shows the inside of the seam plate after the temperature-pressure responsive acid-soluble pressure-bearing sealing material of Example 1 was subjected to reverse pressure after being heated at 80℃ for 5 hours. The sealing layer is dense and tightly consolidated and has not been sheared.
[0058] Figure 4B The image shows the interior of the sealing plate after the sealing material of Comparative Example 1 was subjected to reverse pressure under heating at 80℃ for 5 hours. The sealing layer was sheared and destroyed. Detailed Implementation
[0059] In order to provide a clearer understanding of the technical features, objectives and beneficial effects of the present invention, the technical solution of the present invention will now be described in detail below, but it should not be construed as limiting the scope of implementation of the present invention.
[0060] Example 1
[0061] This embodiment provides a temperature- and pressure-responsive acid-soluble pressure-bearing sealing material, which is composed of four groups of graded resin-coated particles and two groups of pure resin particles. By mass percentage, the components of this temperature- and pressure-responsive acid-soluble pressure-bearing sealing material include: 30% resin-coated calcite (1-3mm) particles, 15% resin-coated calcite (0.5-1mm) particles, 27% resin-coated seashell (1-2mm) particles, 12% resin-coated calcium carbonate (0.01-0.2mm) particles, 8% linear phenolic resin particles, and 8% polyamide resin particles.
[0062] The particle size of the two groups of pure resin particles is 0.2-0.5 mm, and the softening point is 70-90℃; each resin-coated particle contains an internal phase and an external phase.
[0063] By mass, the internal phase raw material for resin-coated calcite (1-3 mm) particles is 74 parts calcite (particle size 1-3 mm), and the external phase raw material is: 15 parts modified solid epoxy resin with triazine group (softening point 70-90℃) (modified resin), 7 parts diaminodiphenylmethane curing agent, 3 parts benzyltriethylammonium chloride curing accelerator, and 1 part calcium stearate lubricant.
[0064] The synthesis method of modified solid epoxy resin with triazine group (softening point 70-90℃) is as follows:
[0065] (1) Under nitrogen protection, 132g of hexahydrotrimethyl-S-triazine was reacted with 643g of epichlorohydrin at 120℃ for 2h, and then unreacted epichlorohydrin was removed by vacuum distillation to obtain the intermediate.
[0066] (2) Mix 20g of E12 solid epoxy resin, 8g of bisphenol A and 20g of the intermediate obtained in step 1, dissolve in 200g of xylene solvent, add 0.06g of triphenylphosphine catalyst, and react at 125℃ for 4h.
[0067] (3) After cooling the reactants from step (2) to room temperature, remove the unreacted solvent by vacuum distillation, wash with water 3-5 times to remove the catalyst, and finally obtain a modified solid epoxy resin with triazine group with a softening point of 70-90℃.
[0068] The internal phase raw material for resin-coated calcite (0.5-1mm) particles is 70 parts of calcite (particle size 0.5-1mm), and the external phase raw material is: 17 parts of modified solid epoxy resin with triazine group (softening point 70-90℃), 8 parts of diaminodiphenylmethane curing agent, 4 parts of benzyltriethylammonium chloride curing accelerator, and 1 part of calcium stearate lubricant.
[0069] The inner phase raw material of the resin-coated shell (1-2mm) particles is 69 parts of calcite (particle size 1-2mm), and the outer phase raw material is: 17 parts of modified solid epoxy resin with triazine group (softening point 70-90℃), 9 parts of diaminodiphenylmethane curing agent, 4 parts of benzyltriethylammonium chloride curing accelerator, and 1 part of calcium stearate lubricant.
[0070] The internal phase raw material for resin-coated calcium carbonate (0.01-0.2 mm) particles is 64 parts of calcite (particle size 0.01-0.2 mm), and the external phase raw material is: 20 parts of modified solid epoxy resin with triazine group (softening point 70-90℃), 10 parts of diaminodiphenylmethane curing agent, 5 parts of benzyltriethylammonium chloride curing accelerator, and 1 part of calcium stearate lubricant.
[0071] The preparation method of the above-mentioned resin-coated particles is as follows: heat the modified resin to 125°C to melt it, mix the molten modified resin with a cleaned and dried inert material, so that the modified resin coats the surface of the inert material; then cool it down to 90°C of the modified resin, add a curing agent and a curing accelerator, stir for 10 minutes to mix it thoroughly with the modified resin; then cool it down to 63°C, add a lubricant and stir for 3 minutes; after cooling the mixture, pulverize it to obtain resin-coated particles.
[0072] In this embodiment, the aforementioned temperature- and pressure-responsive acid-soluble pressure-bearing plugging material is added to the drilling fluid to form a plugging slurry. The amount of the temperature- and pressure-responsive acid-soluble pressure-bearing plugging material added is 25% (w / v) of the drilling fluid volume. The drilling fluid formula is: water + 2.5% (w / v) bentonite + 0.5% (w / v) xanthan gum + 1.5% (w / v) low-viscosity polyanionic cellulose sodium salt + 7% (w / v) KCl + 78% (w / v) barite. The density of the drilling fluid is approximately 1.5 g / cm³. 3 The apparent viscosity is approximately 20-40 mPa·s.
[0073] Comparative Example 1
[0074] This comparative example provides a sealing material with the same particle size and ratio of each component as the temperature and pressure responsive acid-soluble pressure-bearing sealing material of Example 1. The only difference is that inert particles are used instead of the resin-coated particles and pure resin particles of Example 1.
[0075] By weight percentage, the components of the sealing material in this comparative example include: 30% calcite (1-3 mm particle size) particles, 15% calcite (0.5-1 mm particle size) particles, 27% shell (1-2 mm particle size) particles, 12% calcium carbonate (0.01-2 mm particle size) particles, and 16% calcium carbonate (0.2-0.5 mm particle size) particles.
[0076] This comparative example also adds the above-mentioned plugging material to the drilling fluid to form a plugging slurry. The drilling fluid composition and the amount of plugging material are the same as in Example 1.
[0077] Example 2
[0078] This embodiment provides a temperature- and pressure-responsive acid-soluble pressure-bearing sealing material, which is composed of 6 groups of graded resin-coated particles and 3 groups of pure resin particles. By mass percentage, the components of this temperature- and pressure-responsive acid-soluble pressure-bearing sealing material include: 25% resin-coated calcite (3-5mm) particles, 12% resin-coated calcite (1-3mm) particles, 13% resin-coated calcite (0.5-1mm) particles, 27% resin-coated shell (3-5mm) particles, 5% resin-coated shell (1-3mm) particles, 12% resin-coated calcium carbonate (0.01-0.2mm) particles, 5% linear phenolic resin particles, 5% polyamide resin particles, and 5% modified solid epoxy resin particles with triazine groups.
[0079] Among them, the particle size of the above three groups of pure resin particles is 0.2-0.5 mm, and the softening point is 110-130℃; each resin-coated particle contains an internal phase and an external phase.
[0080] By mass, the internal phase raw material for resin-coated calcite (3-5mm) particles is 72 parts calcite (particle size 3-5mm), and the external phase raw material is: 12 parts modified solid epoxy resin with triazine group (softening point 110-130℃) (modified resin), 6 parts hexahydrophthalic anhydride curing agent, 4 parts pyromellitic anhydride curing agent, 1 part triethylamine hydrochloride curing accelerator, 2 parts 2-ethyl-4-methylimidazolium curing accelerator, and 1 part calcium stearate lubricant;
[0081] The synthesis method of modified solid epoxy resin with triazine group (softening point 110-130℃) is as follows:
[0082] (1) Under nitrogen protection, 132g of hexahydrotrimethyl-S-triazine and 523g of epichlorohydrin were reacted at 120°C for 2h. Then, unreacted epichlorohydrin was removed by vacuum distillation to obtain the intermediate.
[0083] (2) Mix 20g of E06 solid epoxy resin, 6g of bisphenol A and 18g of the intermediate obtained in step 1, dissolve in 200g of xylene solvent, add 0.21g of triethanolamine catalyst, and react at 120℃ for 4h.
[0084] (3) After cooling the reactants from step (2) to room temperature, remove the unreacted solvent by vacuum distillation, wash with water 3-5 times to remove the catalyst, and finally obtain a modified solid epoxy resin with triazine group with a softening point of 110-130℃.
[0085] The internal phase raw material for resin-coated calcite (1-3mm) particles is 69 parts of calcite (particle size 1-3mm), and the external phase raw material is: 15 parts of modified solid epoxy resin with triazine group (softening point 110-130℃) (modified resin), 6 parts of hexahydrophthalic anhydride curing agent, 6 parts of pyromellitic anhydride curing agent, 1 part of triethylamine hydrochloride curing accelerator, 2 parts of 2-ethyl-4-methylimidazolium curing accelerator, and 1 part of calcium stearate lubricant;
[0086] The internal phase raw material for resin-coated calcite (0.5-1mm) particles is 63 parts of calcite (particle size 0.5-1mm), and the external phase raw material is: 17 parts of modified solid epoxy resin with triazine group (softening point 110-130℃) (modified resin), 8 parts of hexahydrophthalic anhydride curing agent, 7 parts of pyromellitic anhydride curing agent, 2 parts of triethylamine hydrochloride curing accelerator, 2 parts of 2-ethyl-4-methylimidazolium curing accelerator, and 1 part of calcium stearate lubricant;
[0087] The inner phase raw material of the resin-coated shell (3-5mm) particles is 80 parts of shell (particle size 3-5mm), and the outer phase raw material is: 10 parts of modified solid epoxy resin with triazine group (softening point 110-130℃) (modified resin), 4 parts of hexahydrophthalic anhydride curing agent, 4 parts of pyromellitic anhydride curing agent, 1 part of triethylamine hydrochloride curing accelerator, and 1 part of calcium stearate lubricant.
[0088] The inner phase raw material of the resin-coated shell (1-3mm) particles is 72 parts of shell (particle size 1-3mm), and the outer phase raw material is: 17 parts of modified solid epoxy resin with triazine group (softening point 110-130℃) (modified resin), 4 parts of hexahydrophthalic anhydride curing agent, 4 parts of pyromellitic anhydride curing agent, 2 parts of 2-ethyl-4-methylimidazolium curing accelerator, and 1 part of calcium stearate lubricant.
[0089] The internal phase raw material for resin-coated calcium carbonate (0.01-0.2 mm) particles is 55 parts of calcium carbonate (particle size 0.01-0.2 mm), and the external phase raw material is: 20 parts of modified solid epoxy resin with triazine group (softening point 110-130℃) (modified resin), 10 parts of hexahydrophthalic anhydride curing agent, 9 parts of pyromellitic anhydride curing agent, 3 parts of triethylamine hydrochloride curing accelerator, 2 parts of 2-ethyl-4-methylimidazolium curing accelerator, and 1 part of calcium stearate lubricant.
[0090] The preparation method of the above-mentioned resin-coated particles is as follows: heat the modified resin to 155°C to melt it, mix the molten modified resin with a cleaned and dried inert material, so that the modified resin coats the surface of the inert material; then cool it down to 100°C of the modified resin, add a curing agent and a curing accelerator, stir for 10 minutes to make it fully mixed with the modified resin; then cool it down to 70°C, add a lubricant and stir for 3 minutes; after cooling the mixture, pulverize it to obtain resin-coated particles.
[0091] In this embodiment, the aforementioned temperature- and pressure-responsive acid-soluble pressure-bearing plugging material is added to the drilling fluid to form a plugging slurry. The amount of the temperature- and pressure-responsive acid-soluble pressure-bearing plugging material added is 34% (w / v) of the drilling fluid volume. The drilling fluid formulation is: water + 2% (w / v) bentonite + 0.3% (w / v) zwitterionic polymer coating agent FA-367 + 1.5% (w / v) low-viscosity polyanionic cellulose sodium salt + 5% (w / v) SMP-2 + 15% (w / v) NaCl + 140% (w / v) barite. The density of the drilling fluid is approximately 1.8 g / cm³. 3 The apparent viscosity is approximately 30-60 mPa·s.
[0092] like Figure 2A and Figure 2B As shown, the surface of the 1-2 mm resin-coated shell particles is a scanning electron microscope image (×300x magnification). The surface of the shell particles becomes dense and smooth after being coated with resin.
[0093] Comparative Example 2
[0094] This comparative example provides a sealing material with the same particle size and ratio of each component as the temperature and pressure responsive acid-soluble pressure-bearing sealing material of Example 2, the only difference being that inert particles are used instead of the resin-coated particles and pure resin particles of Example 1.
[0095] By weight percentage, the components of the sealing material in this comparative example include: 25% calcite (3-5mm particle size) particles, 12% calcite (1-3mm particle size) particles, 13% calcite (0.5-1mm particle size) particles, 15% shell (3-5mm particle size) particles, 5% shell (1-3mm particle size) particles, 15% calcium carbonate (0.01-0.2mm particle size) particles, and 15% calcium carbonate (0.2-0.5mm particle size) particles.
[0096] This comparative example also adds the above-mentioned plugging material to the drilling fluid to form a plugging slurry. The drilling fluid composition and the amount of plugging material are the same as in Example 2.
[0097] Example 3
[0098] This embodiment provides a temperature- and pressure-responsive acid-soluble pressure-bearing sealing material, which is composed of 6 groups of graded resin-coated particles and 3 groups of pure resin particles. By mass percentage, the components of this temperature- and pressure-responsive acid-soluble pressure-bearing sealing material include: 27% resin-coated calcite (2-4 mm) particles, 14% resin-coated calcite (1-2 mm) particles, 13% resin-coated calcite (0.5-1 mm) particles, 10% resin-coated shell (2-4 mm) particles, 5% resin-coated shell (1-2 mm) particles, 13% resin-coated micro manganese powder (0.01-0.2 mm), 8% linear phenolic resin particles, 8% polyamide resin particles, and 2% modified solid epoxy resin particles with triazine groups.
[0099] Among them, the particle size of the above three groups of pure resin particles is 0.2-0.5 mm, and the softening point is 140-160℃; each resin-coated particle contains an internal phase and an external phase; by mass parts, the internal phase raw material of the resin-coated calcite (2-4 mm) particles is 83.5 parts of calcite (particle size 2-4 mm), and the external phase raw material is: 12 parts of modified solid epoxy resin with triazine group (softening point 140-160℃) (modified resin), 1.5 parts of dicyandiamide curing agent, 1 part of m-phenylenediamine curing agent, 1 part of talc lubricant, and 1 part of solid polyvinyl alcohol lubricant;
[0100] The synthesis method of modified solid epoxy resin with triazine group (softening point 140-160℃) is as follows:
[0101] (1) Under nitrogen protection, 132g of hexahydrotrimethyl-S-triazine and 523g of epichlorohydrin were reacted at 120°C for 2h. Then, unreacted epichlorohydrin was removed by vacuum distillation to obtain the intermediate.
[0102] (2) Mix 20g of E03 solid epoxy resin, 10g of bisphenol A and 16g of the intermediate obtained in step 1, dissolve in 200g of xylene solvent, add 0.17g of trimethylbutylamine catalyst, and react at 130℃ for 6h.
[0103] (3) After cooling the reactants from step (2) to room temperature, remove the unreacted solvent by vacuum distillation, wash with water 3-5 times to remove the catalyst, and finally obtain a modified solid epoxy resin with triazine group with a softening point of 140-160℃.
[0104] The internal phase raw material for resin-coated calcite (1-2mm) particles is 82.5 parts of calcite (particle size 1-2mm), and the external phase raw material is: 13 parts of modified solid epoxy resin with triazine group (softening point 140-160℃) (modified resin), 1.5 parts of dicyandiamide curing agent, 1 part of m-phenylenediamine curing agent, 1 part of talc lubricant, and 1 part of solid polyvinyl alcohol lubricant.
[0105] The internal phase raw material for resin-coated calcite (0.5-1mm) particles is 80 parts of calcite (particle size 0.5-1mm), and the external phase raw material is: 15 parts of modified solid epoxy resin with triazine group (softening point 140-160℃) (modified resin), 2 parts of dicyandiamide curing agent, 1 part of m-phenylenediamine curing agent, 1 part of talc lubricant, and 1 part of solid polyvinyl alcohol lubricant.
[0106] The inner phase raw material of the resin-coated shell (2-4mm) particles is 86 parts of shell (particle size 2-4mm), and the outer phase raw material is: 10 parts of modified solid epoxy resin with triazine group (softening point 140-160℃) (modified resin), 1 part of dicyandiamide curing agent, 1 part of m-phenylenediamine curing agent, 1 part of talc lubricant, and 1 part of solid polyvinyl alcohol lubricant.
[0107] The inner phase raw material of the resin-coated shell (1-2mm) particles is 80 parts of shell (particle size 1-2mm), and the outer phase raw material is: 15 parts of modified solid epoxy resin with triazine group (softening point 140-160℃) (modified resin), 2 parts of dicyandiamide curing agent, 1 part of m-phenylenediamine curing agent, 1 part of talc lubricant, and 1 part of solid polyvinyl alcohol lubricant.
[0108] The internal phase raw material for resin-coated micro manganese powder (0.01-0.2mm) is 76 parts of micro manganese powder (particle size 0.01-0.2mm), and the external phase raw material is: 18 parts of modified solid epoxy resin with triazine group (softening point 140-160℃) (modified resin), 2 parts of dicyandiamide curing agent, 2 parts of m-phenylenediamine curing agent, 1 part of talc lubricant, and 1 part of solid polyvinyl alcohol lubricant.
[0109] The preparation method of the above-mentioned resin-coated particles is as follows: heat the modified resin to 180°C to melt it, mix the molten modified resin with a cleaned and dried inert material, so that the modified resin coats the surface of the inert material; then cool it down to 120°C of the modified resin, add a curing agent and a curing accelerator, stir for 10 minutes to make it fully mixed with the modified resin; then cool it down to 55°C, add a lubricant and stir for 3 minutes; after cooling the mixture, pulverize it to obtain resin-coated particles.
[0110] In this embodiment, the aforementioned temperature- and pressure-responsive acid-soluble pressure-bearing plugging material is added to the drilling fluid to form a plugging slurry. The amount of the temperature- and pressure-responsive acid-soluble pressure-bearing plugging material added is 34% (w / v)% of the drilling fluid volume. The drilling fluid formulation is as follows: matrix (volume ratio of 4:1:5# white oil + 40wt% calcium chloride solution) + 4% (w / v) amide primary emulsifier + 2% (w / v) amide secondary emulsifier + 2% (w / v) organic clay + 4% (w / v) humic acid filtration reducer + 5% (w / v) calcium oxide + 220% (w / v) barite (each percentage is based on the weight of the matrix). The density of the drilling fluid is approximately 2.0 g / cm³. 3 The apparent viscosity is approximately 40-70 mPa·s.
[0111] Comparative Example 3
[0112] This comparative example provides a sealing material with the same particle size and ratio of each component as the temperature and pressure responsive acid-soluble pressure-bearing sealing material of Example 3, the only difference being that inert particles are used instead of the resin-coated particles and pure resin particles of Example 1.
[0113] By weight percentage, the components of the sealing material in this comparative example include: 27% calcite (2-4 mm particle size) particles, 14% calcite (1-3 mm particle size) particles, 13% calcite (0.5-1 mm particle size) particles, 10% shell (3-5 mm particle size) particles, 5% shell (1-3 mm particle size) particles, 13% micro manganese powder (0.01-0.2 mm particle size) particles, and 18% calcium carbonate (0.2-0.5 mm particle size) particles.
[0114] This comparative example also adds the above-mentioned plugging material to the drilling fluid to form a plugging slurry. The drilling fluid composition and the amount of plugging material are the same as in Example 3.
[0115] Example 4
[0116] This embodiment provides a temperature- and pressure-responsive acid-soluble pressure-bearing sealing material, which is composed of 6 groups of graded resin-coated particles and 3 groups of pure resin particles. By mass percentage, the components of this temperature- and pressure-responsive acid-soluble pressure-bearing sealing material include: 30% resin-coated calcite (5-8mm) particles, 18% resin-coated ceramsite (2-4mm) particles, 13% resin-coated calcite (0.5-1mm) particles, 5% resin-coated shell (2-4mm) particles, 3% resin-coated shell (1-2mm) particles, 19% resin-coated calcium carbonate (0.01-0.2mm) particles, 2% linear phenolic resin particles, 2% polyamide resin particles, and 8% triazine-modified solid epoxy resin particles.
[0117] Among them, the particle size of the above three groups of pure resin particles is 0.2-0.5 mm, and the softening point is 90-120℃; each resin-coated particle contains an internal phase and an external phase.
[0118] By mass, the internal phase raw materials for resin-coated calcite particles are 75 parts of calcite (particle size 5-8 mm) and 4 parts of expanded graphite (particle size 5-8 mm); the external phase raw materials are: 15 parts of modified solid epoxy resin with triazine group (softening point 90-120℃) (modified resin), 4 parts of diaminodiphenyl sulfone curing agent, 1 part of imidazole salt complex curing accelerator, and 1 part of zinc stearate lubricant.
[0119] The synthesis method of modified solid epoxy resin with triazine group (softening point 90-120℃) is as follows:
[0120] (1) Under nitrogen protection, 132g of hexahydrotrimethyl-S-triazine and 478g of epichlorohydrin were reacted at 120°C for 2h. Then, unreacted epichlorohydrin was removed by vacuum distillation to obtain the intermediate.
[0121] (2) Mix 20g of E12 solid epoxy resin, 9g of bisphenol A and 16g of the intermediate obtained in step 1, dissolve in 200g of xylene solvent, add 0.09g of triethanolamine and 0.03g of trimethylbutylamine catalyst, and react at 110℃ for 3.5h.
[0122] (3) After cooling the reactants from step (2) to room temperature, remove the unreacted solvent by vacuum distillation, wash with water 3-5 times to remove the catalyst, and finally obtain a modified solid epoxy resin with triazine group with a softening point of 90-120℃.
[0123] The internal phase raw materials of the resin-coated ceramsite (2-4mm) particles are 78 parts of lightweight ceramsite (particle size 2-4mm) and 2 parts of expanded graphite (particle size 2-4mm). The external phase raw materials are: 14 parts of modified solid epoxy resin with triazine group (softening point 90-120℃) (modified resin), 4 parts of diaminodiphenyl sulfone curing agent, 1 part of imidazole salt complex curing accelerator, and 1 part of zinc stearate lubricant.
[0124] The internal phase raw material for resin-coated calcite (0.5-1mm) particles is 79 parts of calcite (particle size 0.5-1mm), and the external phase raw material is: 15 parts of modified solid epoxy resin with triazine group (softening point 90-120℃) (modified resin), 4 parts of diaminodiphenyl sulfone curing agent, 1 part of imidazole salt complex curing accelerator, and 1 part of zinc stearate lubricant.
[0125] The inner phase raw material of the resin-coated shell (2-4mm) particles is 83 parts of shell (particle size 2-4mm), and the outer phase raw material is: 12 parts of modified solid epoxy resin with triazine group (softening point 90-120℃) (modified resin), 3 parts of diaminodiphenyl sulfone curing agent, 1 part of imidazole salt complex curing accelerator, and 1 part of zinc stearate lubricant.
[0126] The inner phase raw material of the resin-coated shell (1-2mm) particles is 78 parts of shell (particle size 1-2mm), and the outer phase raw material is: 16 parts of modified solid epoxy resin with triazine group (softening point 90-120℃) (modified resin), 4 parts of diaminodiphenyl sulfone curing agent, 1 part of imidazole salt complex curing accelerator, and 1 part of zinc stearate lubricant.
[0127] The internal phase raw material for resin-coated calcium carbonate (0.01-0.2 mm) particles is 75 parts of calcium carbonate (particle size 0.01-0.2 mm), and the external phase raw material is: 18 parts of modified solid epoxy resin with triazine group (softening point 90-120℃) (modified resin), 5 parts of diaminodiphenyl sulfone curing agent, 1 part of imidazole salt complex curing accelerator, and 1 part of zinc stearate lubricant.
[0128] The preparation method of the above-mentioned resin-coated particles is as follows: heat the modified resin to 150°C to melt it, mix the molten modified resin with a cleaned and dried inert material, so that the modified resin coats the surface of the inert material; then cool it down to 90°C of the modified resin, add a curing agent and a curing accelerator, stir for 10 minutes to make it fully mixed with the modified resin; then cool it down to 55°C, add a lubricant and stir for 3 minutes; after cooling the mixture, pulverize it to obtain resin-coated particles.
[0129] In this embodiment, the aforementioned temperature- and pressure-responsive acid-soluble pressure-bearing plugging material is added to the drilling fluid to form a plugging slurry. The amount of the temperature- and pressure-responsive acid-soluble pressure-bearing plugging material added is 40% (w / v) of the drilling fluid volume. The drilling fluid formula is: water + 3% (w / v) bentonite + 0.5% (w / v) FA-367 + 1.0% (w / v) low-viscosity polyanionic cellulose sodium salt + 43% (w / v) barite. The density of the drilling fluid is approximately 1.3 g / cm³. 3 The apparent viscosity is approximately 15-30 mPa·s.
[0130] Comparative Example 4
[0131] This comparative example provides a sealing material with the same particle size and ratio of each component as the temperature and pressure responsive acid-soluble pressure-bearing sealing material of Example 4, except that inert particles are used instead of the resin-coated particles and pure resin particles of Example 1.
[0132] By weight percentage, the components of the sealing material in this comparative example include: 30% calcite (5-8mm particle size) particles, 18% ceramsite (2-4mm particle size) particles, 13% calcite (0.5-1mm particle size) particles, 5% shell (2-4mm particle size) particles, 3% shell (1-2mm particle size) particles, 19% calcium carbonate (0.01-0.2mm particle size) particles, and 12% calcium carbonate (0.2-0.5mm particle size) particles.
[0133] This comparative example also adds the above-mentioned plugging material to the drilling fluid to form a plugging slurry. The drilling fluid composition and the amount of plugging material are the same as in Example 4.
[0134] Comparative Example 5
[0135] This comparative example provides a sealing material with the same particle size and ratio of each component as the temperature and pressure responsive acid-soluble pressure-bearing sealing material of Example 4. The only differences are: ① the resin used to coat the particles is unmodified solid epoxy resin, and ② no pure resin particles are added to the formulation.
[0136] This comparative example provides a temperature- and pressure-responsive, acid-soluble, pressure-bearing sealing material, which consists of six groups of graded resin-coated particles and one group of calcium carbonate particles. By mass percentage, the components of this temperature- and pressure-responsive, acid-soluble, pressure-bearing sealing material include: 30% resin-coated calcite (5-8 mm) particles, 18% resin-coated ceramic particles (2-4 mm) particles, 13% resin-coated calcite (0.5-1 mm) particles, 5% resin-coated shell particles (2-4 mm) particles, 3% resin-coated shell particles (1-2 mm) particles, and 12% calcium carbonate (0.2-0.5 mm) particles. This comparative example has the same particle size ratio and gradation as Example 4, the only differences being: ① the resin used for the resin-coated particles is unmodified solid epoxy resin, and ② the pure resin particles in the formulation are replaced with calcium carbonate particles of the same particle size.
[0137] By mass, the internal phase raw materials for resin-coated calcite (5-8 mm) particles are 75 parts calcite (5-8 mm particle size) and 4 parts expanded graphite (5-8 mm particle size); the external phase raw materials are: 15 parts solid epoxy resin E12 (softening point 90-120℃), 4 parts diaminodiphenyl sulfone curing agent, 1 part imidazole salt complex curing accelerator, and 1 part zinc stearate lubricant.
[0138] The internal phase raw materials of the resin-coated ceramsite (2-4mm) particles are 78 parts of lightweight ceramsite (particle size 2-4mm) and 2 parts of expanded graphite (particle size 2-4mm). The external phase raw materials are: 14 parts of solid epoxy resin E12 (softening point 90-120℃), 4 parts of diaminodiphenyl sulfone curing agent, 1 part of imidazole salt complex curing accelerator, and 1 part of zinc stearate lubricant.
[0139] The internal phase raw material of the resin-coated calcite (0.5-1mm) particles is 79 parts of calcite (particle size 0.5-1mm), and the external phase raw material is: 15 parts of solid epoxy resin E12 (softening point 90-120℃), 4 parts of diaminodiphenyl sulfone curing agent, 1 part of imidazole salt complex curing accelerator, and 1 part of zinc stearate lubricant.
[0140] The inner phase raw material of the resin-coated shell (2-4mm) particles is 83 parts of shell (particle size 2-4mm), and the outer phase raw material is: 12 parts of solid epoxy resin E12 (softening point 90-120℃), 3 parts of diaminodiphenyl sulfone curing agent, 1 part of imidazole salt complex curing accelerator, and 1 part of zinc stearate lubricant.
[0141] The inner phase raw material of the resin-coated shell (1-2mm) particles is 78 parts of shell (particle size 1-2mm), and the outer phase raw material is: 16 parts of solid epoxy resin E12 (softening point 90-120℃), 4 parts of diaminodiphenyl sulfone curing agent, 1 part of imidazole salt complex curing accelerator, and 1 part of zinc stearate lubricant.
[0142] The internal phase raw material of the resin-coated calcium carbonate (0.01-0.2mm) particles is 75 parts of calcium carbonate (particle size 0.01-0.2mm), and the external phase raw material is: 18 parts of solid epoxy resin E12 (softening point 90-120℃), 5 parts of diaminodiphenyl sulfone curing agent, 1 part of imidazole salt complex curing accelerator, and 1 part of zinc stearate lubricant.
[0143] The synthesis method of the resin-coated particles is the same as that in Example 4.
[0144] Experimental Example 1
[0145] This experimental example is used to test the compressive strength of the solidified plugging material of the above embodiments and comparative examples.
[0146] The test method is as follows: a cylindrical steel mold is selected, 30g of the above-mentioned sealing material is added according to the formula ratio of the sealing material, the sealing material is squeezed for 20 minutes under different pressures, the mold is then sealed, heated at a set temperature for a certain time, and after cooling, the cylindrical sealing material solidified body is taken out, and the maximum compressive strength of the solidified body is tested using a uniaxial compressive strength tester.
[0147] The test results are shown in Table 1.
[0148] Table 1 Compressive strength of the solidified plugging material
[0149]
[0150]
[0151] The results show that the plugging materials in Examples 1-4 exhibit dual temperature and pressure response characteristics, and can only solidify under high temperature and extrusion conditions (as shown in the attached figure). Figure 1 By adjusting the resin coating layer formulation and the pure resin particle formulation, the solidification performance under temperatures of 80-150℃ and extrusion pressures of 10-20MPa can be controlled. The inert particles in Comparative Examples 1-4 have no cementing performance. Comparative Example 5, which does not contain pure resin particles, has a significantly lower cementing strength than Example 4.
[0152] Experimental Example 2
[0153] This experimental example is used to test the acid solubility of the sealing materials after solidification in the above embodiments and comparative examples.
[0154] The test method is as follows: A cylindrical steel mold is selected, and 20g of the above-mentioned sealing material is added according to the formula ratio. The sealing material is squeezed under a pressure of 10MPa for 20min. Then the mold is sealed and heated at a set temperature for a certain time. After cooling, the cylindrical sealing material solidified body is taken out and the mass of the solidified body is weighed. Then it is placed in 100mL of 15% hydrochloric acid solution and stirred at 50℃ for 2h. After cooling, it is passed through a 325-mesh sieve, the insoluble matter is collected, washed with water and dried, and the acid solubility rate is calculated.
[0155] The test results are shown in Table 2.
[0156] Table 2 Acid solubility of the solidified plugging material
[0157] Example 1 19.5 2.4 87.69% Comparative Example 1 20.1 1.4 93.03% Example 2 20.7 3.2 84.54% Comparative Example 2 20.3 1.2 94.09% Example 3 20.5 2.9 85.85% Comparative Example 3 19.8 1.6 91.92% Example 4 20.6 3.9 81.06% Comparative Example 4 20.5 3.4 83.41% Comparative Example 5 20.3 16.2 20.20%
[0158] The results showed that the acid solubility of Examples 1-4 and Comparative Examples 1-4 was basically the same, while the acid solubility of Example 4 and Comparative Example 5 differed significantly. This indicates that the epoxy resin coating with triazine groups can be effectively acid-soluble after curing, but conventional solid epoxy resin coatings are difficult to acid-soluble and hinder the acid solubility of internal calcite, shell and other particles.
[0159] Experimental Example 3
[0160] This experimental example is used to test the positive and negative pressure resistance of the sealing materials used in the above embodiments and comparative examples.
[0161] The testing method includes the following steps:
[0162] (1) Drilling fluid preparation: Prepare 6L of drilling fluid according to the drilling fluid formula in the above examples and comparative examples for later use;
[0163] (2) Preparation of plugging slurry: Take 1500 mL of drilling fluid prepared in step (1), add the plugging materials of the above examples and comparative examples to the drilling fluid according to the proportions described in the examples and comparative examples, stir with an electric stirrer for 30 min, and obtain the corresponding plugging slurry respectively.
[0164] (3) Using a DL-type leak-stopping instrument (a conventional device in this field), select a wedge template with a certain crack width, and insert the template into the test cup with the large crack width end face connected to the test cup (the same below) to form a test assembly; take 2000mL of the leak-stopping slurry prepared in step (2) and pour it into the leak-stopping slurry vessel, open the control valve, increase the pressure by 1MPa each time, stabilize the pressure for 5min, continue to increase the pressure until it reaches 10MPa, stabilize the pressure for 30min, release the pressure, and clean the vessel and pipeline;
[0165] (4) Positive pressure bearing capacity test:
[0166] Take out the wedge template from the leak plugging test in step (3) (without disassembling it), clean the surface of the wedge template, put it into a high-temperature and high-pressure sealed steel tank filled with drilling fluid, seal and heat it for 5 hours at a certain temperature, take out the template and cool it to room temperature; put the cooled wedge template into the test cup in the positive direction, take 2000mL of the water-based drilling fluid prepared in step (1) and inject it into the leak plugging slurry vessel, pressurize it to 1.0MPa, heat the leak plugging slurry vessel to a certain temperature; open the control valve, increase the pressure by 1MPa each time, stabilize the pressure for 5 minutes, continue to pressurize until leakage occurs again, and record the positive pressure bearing capacity;
[0167] (5) Reverse pressure bearing capacity test:
[0168] Repeat step (3), remove the wedge template from the leak plugging test in step (3) (without disassembling), clean the surface of the wedge template, put it into a high-temperature and high-pressure sealed steel tank filled with drilling fluid, seal and heat for 5 hours at a certain temperature, remove the template and cool it to room temperature; put the cooled wedge template back into the test cup, take 2000 mL of the water-based drilling fluid prepared in step (1) and inject it into the leak plugging slurry vessel, pressurize it to 1.0 MPa, heat the leak plugging slurry vessel to a certain temperature; open the control valve, increase the pressure by 1 MPa each time, stabilize the pressure for 5 minutes, continue to pressurize until leakage occurs again, and record the reverse pressure resistance.
[0169] The test results are shown in Table 3.
[0170] Table 3. Results of positive and negative pressure tests on sealing grout with added sealing material.
[0171]
[0172]
[0173] The results show that the temperature- and pressure-responsive acid-soluble plugging material of the present invention exhibits temperature and pressure response characteristics in terms of pressure-bearing plugging effect. Examples 1-4 and Comparative Example 5, which have resin coating layers, demonstrate excellent positive pressure resistance and reverse pressure resistance due to the adhesive bonding effect of the plugging material under high temperature and extrusion conditions, thus outperforming conventional inert bridging plugging material formulations of Comparative Examples 1-4 (as shown in the appendix). Figure 3 Meanwhile, under conditions below the response temperature, the sealing layer formed in the joint plate in Examples 1-4 did not show significant bonding, the sealing layer was sheared and destroyed, and the leak-stopping performance was basically the same as that of Comparative Examples 1-4, with a reverse bearing pressure of 0 (as shown in the attached figure). Figure 4A and 4B Comparative Example 5, due to its use of an unmodified solid epoxy resin coating layer and the absence of pure resin particles, exhibits lower bonding strength than Example 4, resulting in a significant decrease in reverse pressure resistance.
Claims
1. A temperature- and pressure-responsive acid-soluble pressure-bearing sealing material, comprising resin-coated particles and pure resin particles; The resin-coated particles comprise an internal phase and an external phase. By mass, the raw material for the internal phase comprises 60-90 parts of an inert material, and the raw material for the external phase comprises: The mixture comprises 10-20 parts of modified resin, 1-20 parts of curing agent, and 1-5 parts of lubricant; wherein the modified resin is a modified solid epoxy resin with triazine groups. The pure resin particles are thermoplastic solid resin particles; The preparation method of the modified solid epoxy resin with triazine groups includes the following steps: (1) Under nitrogen protection, hexahydrotrimethyl-S-triazine was reacted with epichlorohydrin for the first reaction at 100-120℃ for 2-5 h to obtain an intermediate. Unreacted epichlorohydrin was then removed by vacuum distillation. (2) Mix solid epoxy resin, bisphenol A and the intermediate in a solvent, add a catalyst, and carry out a second reaction at 110-130°C for 4-6 hours to obtain the modified solid epoxy resin with triazine group. Wherein, the molar ratio of hexahydrotrimethyl-S-triazine to epichlorohydrin is 1:5-1:8; The mass ratio of the solid epoxy resin: bisphenol A: intermediate is 1:0.3-0.5:0.7-1; The solid epoxy resin is a high softening point solid epoxy resin, and the solid epoxy resin is selected from solid epoxy resin E12, solid epoxy resin E06 or solid epoxy resin E03.
2. The temperature- and pressure-responsive acid-soluble pressure-bearing sealing material according to claim 1, wherein, The modified solid epoxy resin with triazine groups has a softening point of 70-160℃ and is degradable under acidic conditions.
3. The temperature- and pressure-responsive acid-soluble pressure-bearing sealing material according to claim 1, wherein, The catalyst is added at an amount of 0.05-0.1 wt% of the reactants, and the catalyst includes one or more of triphenylphosphine, triethanolamine, and trimethylbutylamine.
4. The temperature- and pressure-responsive acid-soluble pressure-bearing sealing material according to claim 1, wherein, The inert material includes one or more of the following: lightweight ceramsite, calcite, seashells, calcium carbonate, micro-manganese powder, and expanded graphite; the particle size of the inert material is 0.01 mm to 8 mm.
5. The temperature- and pressure-responsive acid-soluble pressure-bearing sealing material according to claim 1, wherein, The curing agent includes one or more of the following: dicyandiamide, m-phenylenediamine, diaminodiphenylmethane, diaminodiphenyl sulfone, phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, and pyromellitic anhydride.
6. The temperature- and pressure-responsive acid-soluble pressure-bearing sealing material according to claim 1, wherein, The lubricant includes one or a combination of calcium stearate, zinc stearate, solid polyvinyl alcohol, and talc.
7. The temperature- and pressure-responsive acid-soluble pressure-bearing sealing material according to claim 1, wherein, The raw materials for the external phase also include 0-5 parts of a curing accelerator, which includes one or more of the following: triethylamine hydrochloride, benzyltriethylammonium chloride, 2-ethyl-4-methylimidazolium, imidazolium salt complex, and acetylhydrazine.
8. The temperature- and pressure-responsive acid-soluble pressure-bearing sealing material according to claim 1, wherein, The method for preparing the resin-coated particles includes the following steps: heating the modified resin to melt, mixing the molten modified resin with an inert material to coat the surface of the inert material with the modified resin; cooling the modified resin to its softening point, adding a curing agent and preferably a curing accelerator and mixing thoroughly; cooling the mixture again, adding a lubricant and mixing; cooling the mixture and then pulverizing it to obtain the resin-coated particles.
9. The temperature- and pressure-responsive acid-soluble pressure-bearing sealing material according to claim 8, wherein, The heating temperature for melting the modified resin is 10-20℃ above the softening point; the stirring time after adding the curing agent is 3-10 minutes; the stirring time after adding the lubricant is 1-3 minutes.
10. The temperature- and pressure-responsive acid-soluble pressure-bearing sealing material according to claim 1, wherein, The temperature and pressure responsive acid-soluble pressure-bearing sealing material includes graded resin-coated particles and at least one pure resin particle, with the total weight ratio of the resin-coated particles to the total weight of the pure resin particles being 8-9:1-2.
11. The temperature- and pressure-responsive acid-soluble pressure-bearing sealing material according to claim 10, wherein, The raw material for the pure resin particles is a thermoplastic solid resin, and the softening point of the thermoplastic solid resin is 80-150℃.
12. The temperature- and pressure-responsive acid-soluble pressure-bearing sealing material according to claim 11, wherein, The thermoplastic solid resin includes one or more of the following: modified solid epoxy resin with triazine groups, linear phenolic resin, polyurethane, polyamide resin, and acrylic resin.
13. The temperature- and pressure-responsive acid-soluble pressure-bearing sealing material according to claim 10, wherein, The particle size distribution range of the graded resin-coated particles is 0.01-3 mm; the particle size of the pure resin particles is 0.01-3 mm.
14. The application of the temperature-pressure responsive acid-soluble pressure-bearing plugging material according to any one of claims 1-13 in pressure-bearing plugging of reservoir sections.
15. The application according to claim 14, wherein, The application temperature is 80-150℃.
16. The application according to claim 14, wherein, The acid solubility of the temperature-pressure responsive acid-soluble pressure-bearing sealing material after solidification is >80%.
17. The application according to claim 14, wherein, The temperature- and pressure-responsive acid-soluble pressure-bearing plugging material is added to the drilling fluid, which is either water-based or oil-based. Based on the total volume of the drilling fluid, the total mass of the temperature- and pressure-responsive acid-soluble pressure-bearing plugging material is 25-40 (w / v).
18. The application according to claim 14, wherein, Drilling fluids with added temperature- and pressure-responsive acid-soluble pressure-bearing plugging materials can withstand positive or negative pressure of ≥15MPa at a 1-8mm crack width.
Citation Information
Patent Citations
Anti-backflow leak-stopping agent, preparation method and applications thereof
CN103087687A
Bridging leak-stopping agent for fractured reservoir, and preparation method and application thereof
CN106281272A
Acid-soluble cement paste, and preparation method and application thereof
CN108929099A
An oil-soluble temperature-sensitive resin plugging agent for reservoir protection, its preparation method and application
CN113480984B
Epoxy resin prepolymer containing hexahydrotriazine structure and preparation method of epoxy resin prepolymer
CN108191840A